ORGANIZATION ROBOTS; TREND TO POST-HUMAN RESOURCES MANAGEMENT (POST-HRM) - Omer, Soran Kakarash (Journal of process management and new technologies, 2018)
Abstract This study aims to investigative roles of organization robots to re-design concepts and theories of human resources management in to new designation of Post-human resources management (Post-HRM). As well as it's constructed on the data's taken from different books on the related topics, public websites and other statistics, various journals, newspapers and which are collected from them. Considerable information has been gathered from these sources thus allowing for appropriate analysis, comparing, accumulation, explanation. Therefore it's a resolution to isolate and categorize of the potential sources of robots then its impact on human resources management. The main finding is the organizational robotics have an effect on the most important concepts of theories of the human resources management especially human resources planning, employment, training and performance appraisal system for organizational regulations, finally  they have ability  to effect of costs, productivity , profitability of company and  organizational performance